An energy-aware RPL for wireless sensor networks with ambient energy harvesting - Limjoco, Wilbert Jethro R.; Tiglao, Nestor Michael C. (Quezon City College of Engineering, University of the Philippines Diliman, 2017)
Wireless Sensor Networks (WSNs) allow us to monitor and control large systems such as ecological systems, electricity grids, agricultural land, industrial facilities, and urban areas. Implementation of WSNs are usually on wide and remote areas, thus making the use of battery operated sensor nodes difficult, if not impossible, as replacing the batteries in such scenarios is a daunting task. Thus, there is a need to make use of self-sustaining energy harvesting sensor nodes. However, the Routing Protocol for Low Power and Lossy Networks (RPL), the de facto standard routing protocol for WSNs, assumes that there is a constant supply of energy for all sensors, and that it does not use energy as its routing metric. This assumption has already been disproved as nodes would need to disconnect from the network periodically to recharge its battery. Therefore, there is a need to modify RPL to factor in energy in its routing metric to improve the network lifetime. However, factoring in energy alone for routing disregards the performance gains with other metrics, such as Expected Transmission Count (ETX) or Hop Count, as routing to a node with better energy alone may result in selecting a lossy, unreliable, and possibly cyclic path. This study solves this problem by dynamically converting the energy level of a node into an additive penalty to the ETX metric used by RPL's Minimum Rank Hysteresis Objective Function (MRHOF). We modeled RPL using a modified version of the Bellman-Ford algorithm, and emulated it using Cooja with virtual sensor nodes running Contiki OS. Assuming we use a lossless channel and we implement aggressive parent-switching, we have found out in our analytical model simulations that the Average Charge Cycle times and Time of First Node Death increase up to 2.5 times longer as compared to standard RPL for a simple, four node diamond topology and by 5% longer on average for larger, randomly-placed, tree topologies. There is also the consequence of child nodes being disconnected from the network due to the energy balancing in the parent nodes, which lowers the total Packet Delivery Ratio up to 10 percent lower than standard RPL for the simple diamond topology and up to 0.7 percent for the larger tree topologies. However, this is balanced out by the increase in Sending Rate of the parent nodes by 1 percent to 20 percent for both cases due to longer lifetimes. Thus, the total number of packets received from the entire network is the same or up to 8 percent higher for the four node network, and is the same for larger random networks. However, emulation results are inconclusive as they show that adding Energy as part of MRHOF statistically does not have an effect on any metric due to a non-standard implementation of RPL in Contiki OS 3.X.
Thesis (M.S. Electrical Engineering)--University of the Philippines Diliman
Keywords: Wireless sensor networks; Routing protocols (Computer network protocols)